Synthetic Light-Activated Ion Channels for Optogenetic Activation and Inhibition - Beck, Sebastian; Yu-Strzelczyk, Jing; Pauls, Dennis; Constantin, Oana M.; Gee, Christine E.; Ehmann, Nadine; Kittel, Robert J.; Nagel, Georg; Gao, Shiqiang (Frontiers in Neuroscience, 2018)
Optogenetic manipulation of cells or living organisms became widely used in neuroscience following the introduction of the light-gated ion channel channelrhodopsin-2 (ChR2). ChR2 is a non-selective cation channel, ideally suited to depolarize and evoke action potentials in neurons. However, its calcium (Ca2+) permeability and single channel conductance are low and for some applications longer-lasting increases in intracellular calcium might be desirable. Moreover, there is need for an efficient light-gated potassium (K+) channel that can rapidly inhibit spiking in targeted neurons. Considering the importance of Ca2+ and K+ in cell physiology, light-activated Ca2+ permeant and K+-specific channels would be welcome additions to the optogenetic toolbox. Here we describe the engineering of novel light-gated Ca2+ permeant and K+ specific channels by fusing a bacterial photoactivated adenylyl cyclase to cyclic nucleotide-gated channels with high permeability for Ca2+ or for K+, respectively. Optimized fusion constructs showed strong light-gated conductance in Xenopus laevis oocytes and in rat hippocampal neurons. These constructs could also be used to control the motility of Drosophila melanogaster larvae, when expressed in motoneurons. Illumination led to body contraction when motoneurons expressed the light-sensitive Ca2+ permeant channel, and to body extension when expressing the light-sensitive K+ channel, both effectively and reversibly paralyzing the larvae. Further optimization of these constructs will be required for application in adult flies since both constructs led to eclosion failure when expressed in motoneurons.